Spectrophotometric investigations of the binding of ebselen to human serum albumin - (:unkn) unknown (My University, 2005)
Antioksidan özellikte yeni bir ilaç maddesi olan ebselen'in ( 2-phenyl-l,2 benzisoselenazol-3 (2H)~one) insan serum albümini (HSA) ile etkileşimi spektrofotometrik olarak incelendi. Çözücü olarak 0.4 % (v/v) dimetilformamid (DMF) içeren 6.7 mM, pH 7.4 fosfat tamponu ve farklı miktarlarda ebselen-HSA karışımları kullanıldı. Karışım inkübasyonları 25°C de 15 dakika ve 37°C de 30 dakikada gerçekleştirildi. Sonuç spektrumlarındaki düzensiz bir değişim ve bu spektrumlarda izobestik bir noktanın bulunmayışı karışık albumin selenodisülfürlerin oluştuğunu göstermiştir. Ayrıca ebselen ile HSA etkileşimi sonucunda oluşan ürün yapılarının ilaç ve HSA 'nın her ikisinin de konsantrasyonlarına bağlı olduğu saptanmıştır.

The interaction of the novel antioxidant drug ebselen, 2-phenyl-l,2 benzisoselenazol-3 (2H)-one, with human serum albumin (HSA) was investigated by spectrophotometry. 6.7 mM, pH 7.4 of phosphate buffer containing 0,4 % (v/v) dimethylformamide (DMF) was used as the solvent. Various amounts of ebselen and HSA mixtures were used. Incubations of the mixtures were performed for 15 minutes at 25°C and 30 minutes at 37° C. An irregular change and the lack of an isobestic point in the final spectra of the mixtures indicated that the formation of mixed albumin selenodisulfides. It was also determined that the structures of the final products formed from the interactions of the drug and HSA, were depended on both drug and HSA concentrations.
Ebselenin insan serum albuminine bağlanmasının spektrofotometrik olarak incelenmesi
Keywords: Farmakoloji ve Eczacılık